Dynamics of Aromatase and Physiological Indexes in Male Fish as Potential Biomarkers of Anthropogenic Pollution - Guyón, Noelia Fernanda (2016)
Endocrine disruption on aquatic wildlife is being increasingly reported, and the changes in gene aromatase expression are used as indicators. However, naturalfluctuations in brain and gonadal aromatase expression and physiological indexes have not been previously measured in a fish species (Jenynsia multidentata) throughout a complete reproductive cycle, nor the biological effects of anthropogenic inputs on these responses. Accordingly, males were monthly collected over a year in both, a reference and a contaminated site. Physicochemical analyses of water samples were done and reflected a strong anthropogenic impact. Brain aromatase fluctuates along the reproductivecycle of this species and, noticeably, the increase of brain gene expression begins with a 1 month delay in the contaminated site. This mismatch is also evidenced for testes weight. Hepatosomatic index also revealed adverse effects in the polluted site. In turn, the alterations observed in biological responses could be affecting the reproduction of this fish species.